American Bail and the Tinting of Criminal Justice. Issue 4 (31st July 2017) - DABNEY, DEAN A.; PAGE, JOSHUA; TOPALLI, VOLKAN
Abstract: This article analyses the history of bail in the United States in an effort to situate this institution within the general narrative of criminal justice transformation during the 19th and 20th Centuries. We identify core characteristics of American bail (commercialisation, risk assessment, and community supervision) that developed relatively early in the institution's history. Although the structure and processes of American bail was reshaped considerably over time, the spread of neoconservative and neoliberal rationalities did not radically transform the core identity of the institution. Instead, these political logics had a 'tinting effect' on bail, intensifying and altering that which already existed. As such, we frame the case of bail not as a flip from the 'old' to the 'new' penology, but rather of the fusing and reshaping as old practices with new goals, justifications, and methods.